Botanical Survey in Moyo Island, West Nusa Tenggara, Indonesia: Inventory of Flora Collection at Forest - Trimanto Trimanto; Febrina Artauli Siahaan (Journal of Tropical Life Science, 2017)
Nusa Tenggara consists of some small islands, one of them is Moyo Island. The diversity of plant species in this island is not really known for certain. This research was determined to observe the diversity of plant spe-cies in Moyo Island forest. The research was conducted in April 2013 by using floristic analysis method. The characteristic of Moyo Island forest is lowland evergreen rain forest. The results showed there were 60 tree species recorded in Moyo Island forest. There were many fruiting trees and seedling from the trees which show healthy growth, indicated that the plant regeneration in this forest is went well. The diversity of Pteri-dophytes and orchids were not high. Epiphytic fern which often found in the forest were Drynaria quersifolia and Platycerium bifurcatum and terrestrial orchid that dominated in the forest was Nervilia aragoana. Tuber plant was often found in this forest and grew prolifically were Tacca, Dioscorea and Amorphophallus. In coastal area lived a population of Pandanus tectorius. There were three new record plants found. The first was epiphytic orchid: Pteroceras javanica, the second was the epiphytic plant: Hoya verticillata and wild tuber plant: Tacca leontopetaloides.